High-heat-conduction near-net-shaped diamond/copper composite and preparing method thereof - ZENG DECHANG; DONG YINGHU; ZHANG RUIQING (2017)
The invention discloses a high-heat-conduction near-net-shaped diamond/copper composite and a preparing method thereof, and belongs to the field of metal materials. The diamond/copper composite is of a three-dimensional communication structure and is composed of a diamond particle framework, a transition layer, metal copper and surface seepage copper; the preparing method comprises the steps that diamond particles subject to salt-bath plating W are subject to near net shaping, and a pressure-free infiltration method is adopted to prepare the high-heat-conduction composite. The method effectively solves the problems about compatibility of diamond and metal, difficult machining of the diamond/copper composite, poor surface quality, single product shapes, high production cost and the like; the prepared composite is high in compactness, uniform in structure distribution, controllable in interface thickness, high in heat conduction rate, simple in process device, high in operation, low in energy consumption cost,